La laicità dello Stato nella revisione costituzionale della Federazione di Russia: La riforma costituzionale russa del 2020 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The amendments to the Constitution do not concern the secular character of the State and the principle of separation between State and Church. However, there is a conflict between the Constitution and the ordinary laws in force, since the latter violate the principle of state secularism and that of separation between State and Church. The mention of God in the Constitution does not infringe the principle of state secularism since it is not referred to any specific Church or religious confession and does not intend to influence citizens in the religious field.
Keywords: Secularity and Russian Constitution; Confessionalism of ordinary laws; Church and State relations in Russia; Clerical influence on society; Privileged and tolerated religions